Success Rate and Patients’ Satisfaction Following Intradetrusor Dysport Injection in Patients with Detrusor Overactivity: A Comparative Study of Idiopathic and Neurogenic Types of Detrusor Overactivity - Shakeri, Saeed; Mohammadian, Reza; Aminsharifi, Alireza; Ariafar, Ali; Vaghedashti, Jalal; Yazdani, Maryam; Yadollahi, Mahnaz; Emadmarvasti, Vahid; Baharikhoob, Amir (Urology Journal, 2014)
Purpose: To evaluate the efficacy of intradetrusor Dysport (a type of botulinum toxin type A) injection in patients with idiopathic or neurogenic detrusor overactivity, who were refractory to antimuscarinic drugs, and to compare the efficacy of Dysport injection in both groups. Materials and Methods: Twelve patients with neurogenic detrusor overactivity (NDO) and 18patients with idiopathic detrusor overactivity (IDO) participated in this study. All the patientsreceived intravesical injection of 500 units of Dysport. They were followed up for 3 monthsafter injection with maximum cystometric capacity, maximum detrusor filling pressure, andnumber of catheterization or pad usage. Results: After 3 months, the mean maximum cystometric capacity increased from 109.36 ± 24.11 mL to 266.81 ± 97.18 mL (P = .000) in the NDO group and from 192.24 ± 36.21 mL to 272.61 ± 63.37 mL (P = .000) in the IDO group. The mean maximum detrusor filling pressure decreased from 48.14 ± 26.51 cmH2O to 28.91 ± 9.01 cmH2O (P = .005) in the NDO group and from 39.22 ± 9.92 cmH2O to 29.64 ± 10.14 cmH2O (P = .003) in the IDO group. Conclusion: Intradetrusor Dysport injection improved urodynamic parameters and quality of life (QoL) in both groups significantly. We did not find significant difference in QoL or urodynamicparameters between both groups.